Pendekatan Supervisi Direktif dalam Pembinaan Guru Madrasah Tsanawiyah - Abdul Hakim Amrullah; Prim Masrokan; Ahmad Bachtiar Firdaus (J-MPI (Jurnal Manajemen Pendidikan Islam), 2023)
Researchers found that educators were less effective in delivering material, so it was necessary to hold supervision, the principal as a supervisor must understand his duties and must also be able to be open to the teacher by involving the teacher in any planning to be carried out, so that the purpose of this study is that the teacher as an object can understand their duties and make improvements in order to improve the quality and better quality of education for the future. This research uses a qualitative approach, the data collection method is carried out with a naturalistic or interpretive paradigm. Data were collected from natural settings as a direct data source through interviews, observation and documentation. The results of this study are the directive supervision approach at MTs Unggulan Perwanida Blitar based on a behavoristic psychological understanding because some teachers are not qualified in delivering material, it is necessary to provide stimulation so that they can react better. Supervisors can use reinforcement or punishment in providing stimulus. As a means to support the implementation of professional development.